2021
DOI: 10.3389/fncel.2021.665066
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Mast Cells in the Pathophysiology of Pain

Abstract: Mast cells (MCs) are immune cells and are widely distributed throughout the body. MCs are not only classically viewed as effector cells of some allergic diseases but also participate in host defense, innate and acquired immunity, homeostatic responses, and immunoregulation. Mounting evidence indicates that activation of MCs releasing numerous vasoactive and inflammatory mediators has effects on the nervous system and has been involved in different pain conditions. Here, we review the latest advances made about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 116 publications
(144 reference statements)
0
20
0
Order By: Relevance
“…Mast cell-nerve cell spatial contacts has been verified both in vitro and in vivo [ 71 ]. The functional associations between mast cells and nerves have been proven at both the anatomic and the molecular levels [ 72 , 73 , 74 ]. The interaction between nerve cells and mast cells is mutual.…”
Section: Mast Cells and Acupuncture Analgesiamentioning
confidence: 99%
“…Mast cell-nerve cell spatial contacts has been verified both in vitro and in vivo [ 71 ]. The functional associations between mast cells and nerves have been proven at both the anatomic and the molecular levels [ 72 , 73 , 74 ]. The interaction between nerve cells and mast cells is mutual.…”
Section: Mast Cells and Acupuncture Analgesiamentioning
confidence: 99%
“…A substantial body of evidence, based on both animal and human studies, demonstrates that MC-derived NGF plays a pivotal role in the development of hypersensitivity during inflammation. 16,48,49 Therefore, it is no surprise that we found a significant increase in NGF concentration in the vulvar tissue after 24 hours of zymosan administration in the 1st and the 2nd round compared to the saline group. More critically, pretreatment with MCs stabilizer KF prevented the upregulation of NGF concentration in the vulva 24 hours after the zymosan administration in the 1st and the 2nd challenge.…”
mentioning
confidence: 59%
“…In an animal model of CP/CPPS called experimental autoimmune prostatitis (EAP), we have shown the importance of the activation of mast cells and its released tryptases acting on its receptor PAR2 in mediating pain in NOD/ShiLtJ mice. Research in the field of tryptase mediated pain has mostly focused on α/β-tryptases ( 6 ), and little attention has been given to the role played by the δ-tryptase isoform, a truncated protein and a supposedly catalytically inactive form ( 23 , 24 ). Intriguingly, in this study, we observed an elevated level of δ-tryptase in the EPS of patients with CP/CPPS.…”
Section: Discussionmentioning
confidence: 99%
“…Mast cells are a multifaceted and multifunctional immune cell that upon activation releases a plethora of pro-inflammatory mediators such as cytokines and chemokines as well as pain mediators including histamine, proteases (e.g., tryptases), serotonins, neurotrophins, neurotransmitters, and prostaglandin E2 (4)(5)(6)(7)(8)(9)(10). Mast cells also contain preformed pockets of immune mediators and neurotrophins, such as histamine and nerve growth factor (NGF) that can be rapidly released upon activation (11,12).…”
Section: Introductionmentioning
confidence: 99%